Case Report: Biotinidas Defficiency and Report of 3 Cases - Parvaneh Karim-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2003)
Biotinidase deficiency is a rare metabolic disease that is transmitted as an autosomal recessive trait. The clinical manifestations of the disease are, lactic acidosis, alopecia, ataxia, spastic paraplegia, seizure and developmental delay. Other clinical features are erythematous rash, hearing and visual loss. In this 4 article we report 3 patients with complete biotinidase deficiency. First patient was an Infant (3 months old-male) and second patient was an infant (5months old-male) that both of them referred for developmental delay, seizure, alopecia and spastic paraplegia. Laboratory exam showed hyper ammonia, lactic acidosis and the level of Biotinidase was remarkable deficient. All of the symptoms and signs were improved with Biotin. The third patient (8 months old-female) referred for developmental delay and erythematous rash around the orifices. The laboratory exam showed Biotinidase deficiency and all of the symptoms improved with Biotin.